Фізичні та психофізичні особливості відчуття кольору людиною - Бедрата, Р. Р.; Трубчанінова, С. В. (ХНУРЕ, 2024)
The purpose of our work is to study the physical properties of light. We will define the terminology and modern understanding of the nature of photons. The work will present historical facts and hypotheses, the interaction of light with environments, and what physical effect it has on objects in its path. We will analyze in detail the receivers of optical radiation, which include the human eye– the natural optical system, photoreceptors and photoreceptors with charge coupling, and also study some artificial light sources, such as incandescent lamps, gas discharge lamps, LEDs and lasers.
Keywords: колірна ідентифікація; відчуття кольору людиною